BST2 Mediates Osteoblast Differentiation via the BMP2 Signaling Pathway in Human Alveolar-Derived Bone Marrow Stromal Cells - Yoo, Su-Hyang (PLoS One, 2016)
The molecular mechanisms controlling the differentiation of bone marrow stromal stem cells into osteoblasts remain largely unknown. In this study, we investigated whether bone marrow stromal antigen 2 (BST2) influences differentiation toward the osteoblasts lineage. BST2 mRNA expression in human alveolar-derived bone marrow stromal cells (hAD-BMSCs) increased during differentiation into osteoblasts. hAD-BMSCs differentiation into osteoblasts and the mRNA expression of the bone-specific markers alkaline phosphatase, collagen type α 1, bone sialoprotein, osteocalcin, and osterix were reduced by BST2 knockdown using siRNA. Furthermore, BST2 knockdown in hAD-BMSCs resulted in decreased RUNX2 mRNA and protein expression. We hypothesized that BST2 is involved in differentiation of into osteoblasts via the BMP2 signaling pathway. Accordingly, we evaluated the mRNA expression levels of BMP2, BMP receptors (BMPR1 and 2), and the downstream signaling molecules SMAD1, SMAD4, and p-SMAD1/5/8 in BST2 knockdown cells. BMP2 expression following the induction of differentiation was significantly lower in BST2 knockdown cells than in cells treated with a non-targeting control siRNA. Similar results were found for the knockdown of the BMP2 receptor- BMPR1A. We also identified significantly lower expression of SMAD1, SMAD4, and p-SMAD1/5/8 in the BST2 knockdown cells than control cells. Our data provide the first evidence that BST2 is involved in the osteogenic differentiation of bone marrow stromal cells via the regulation of the BMP2 signaling pathway.